Index coding with side information via penalty method in rank minimisation - Goh, You Hui (2018)
Index coding with side information (ICSI) problems can be represented as matrices. These matrices have unique properties with intuitive meaning in its matrix representation. It has been shown by recent studies that minimising the rank of these matrices are equivalent to solving the ICSI problems by finding the minimum index code lengths.